2012
DOI: 10.1177/039463201202500313
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Dependent Clinical and Immunological Efficacy of Sublingual Immunotherapy with Mite Monomeric Allergoid

Abstract: Sublingual immunotherapy with monomeric carbamylated allergoid (LAIS) is an effective and well tolerated treatment of respiratory allergy. The aim of the present study was to correlate the efficacy of two maintenance doses (1000 AU vs 3000 AU) of LAIS with the immunological modulation of allergendriven Thl, Th2 and T regulatory cytokines produced in vitro by PBMCs, in patients suffering from mite allergic rhinitis. Forty-eight consecutive patients with mite allergic rhinitis were recruited. Patients were rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 20 publications
(33 reference statements)
1
15
0
Order By: Relevance
“…The favourable safety profile in this study corresponds to that observed in other studies and has been confirmed in a meta‐analysis . SLIT studies using native allergens are often confounded by the high rate of local side‐effects in the actively treated groups that may unblind patient and investigator.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The favourable safety profile in this study corresponds to that observed in other studies and has been confirmed in a meta‐analysis . SLIT studies using native allergens are often confounded by the high rate of local side‐effects in the actively treated groups that may unblind patient and investigator.…”
Section: Discussionsupporting
confidence: 89%
“…During the treatment phase of 84 days, the patients received daily dosages of a placebo preparation or one of four different active strengths: 300 UA/day, 1000 UA/day, 2000 UA/day or 3000 UA/day (cumulative doses for the 84 days of treatment were 25 200–252 000 UA). According to a publication by Di Gioacchino, 1000 UA correspond to 2.7 μg of group 1 mite allergen and 3000 UA to 8.1 μg of group 1 mite allergen .…”
Section: Methodsmentioning
confidence: 99%
“…The rapid impact of allergoids on in vitro cytokine responses outside of ongoing SIT have remained ill-defined, as the common approach is to assess such responses in PBMCs before/after SIT, a strategy that precludes the comparison of different antigen preparations on the same subject. In studies investigating SIT, increases in IL-10 and IFNγ [13,14] and decreases in IL-4 were described [14] . In our study, the cytokine responses showed substantial variability among the donors, and not all allergic individuals were responsive to either allergen or allergoid in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…[ 22 ] In addition, SLIT tablets ensure better modulation of the drug amount and higher compliance than SLIT drops due to its safety and convenience for transportation, administration, and follow-up. [ 23 ] A majority of current RCTs showed some benefit from immunotherapy on RQLQ and RTSS. SCIT and SLIT are two forms of immunotherapy on allergic rhinitis while SLIT has proven to be potentially safer than SCIT.…”
Section: Discussionmentioning
confidence: 99%